2015
DOI: 10.3109/14767058.2015.1061494
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin as an oxidative stress biomarker in early pregnancy loss

Abstract: Our findings support the theory that possible oxidative stress, a more hypoxic environment and defective placentation lead to increased serum IMA concentrations. These findings may help to shed light on the complicated pathogenesis of early pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…This study has been suggested that in cattle with miscarriage, a significant elevation was found in the serum IMA levels than regular pregnant cattle. This observation was in accordance with the studies done in humans with complicated pregnancies especially in pregnancy losses (Ozdemir et al, 2011, Cengiz et al, 2015. Even if they are different species, the underlying causes of these complicated pregnancies are the similar.…”
Section: Güvensupporting
confidence: 91%
See 2 more Smart Citations
“…This study has been suggested that in cattle with miscarriage, a significant elevation was found in the serum IMA levels than regular pregnant cattle. This observation was in accordance with the studies done in humans with complicated pregnancies especially in pregnancy losses (Ozdemir et al, 2011, Cengiz et al, 2015. Even if they are different species, the underlying causes of these complicated pregnancies are the similar.…”
Section: Güvensupporting
confidence: 91%
“…Increased maternal IMA levels were also seen in recurrent pregnancy loss (Ozdemir et al, 2011) and early pregnancy loss (Cengiz et al, 2015). It is put forward that an intrauterine environment with abnormally reduced amount of blood might be related to abnormal placental development which has a share in the early abortion (Ozdemir et al, 2011).…”
Section: Güvenmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IMA is not only associated with cardiac ischemia, it is also increased in patients with liver cirrhosis, pulmonary embolism, end-stage renal disease, cerebrovascular disease, cancer, systemic sclerosis, preeclampsia, habitual miscarriage, and polycystic ovary syndrome. 7 Up to the present, IMA levels have not yet been examined in patients with primary dysmenorrhea. In the present study, we aimed to determine whether or not there is a relationship between Doppler parameters and IMA levels in uterine arteries in the menstrual and luteal phases.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, it was shown that high IMA is associated with vascular oxidative stress and inflammation. 14,15) Thus, IMA may be a newly nontraditional marker of arterial stiffness.…”
mentioning
confidence: 99%